(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
The study was conducted with the objectives to determine the market availability of animal sourced foods (ASF) and fish, and their share in the supply of biomass and protein through visiting the wet markets of metropolitan and municipality areas of Rajshahi district, Bangladesh. A preset questionnaire was used for recording the biomass weight of different ASF and fish in every four days interval in March, 2016. It was found that the supply of ASF (beef, chevon, chicken and egg) and fish in the metropolitan markets (80.20 and 35.89 t/d, respectively) was significantly higher (P<0.05) than any municipality wet market in the district (7.66 and 3.03 t/d, respectively). The market supply of biomass and its protein value of ASF were 3.64 and 4.33 times higher than fish. The chicken shared the highest amount of protein (28.19 %) followed by fish (26.8%), beef (26.21%), eggs (11.46%) and chevon (7.34%) during the study period. However, this initial work does not include milk, and the wet market of ASF and fish may have seasonal variations which needs to be explored through further research. In addition to them, socioeconomic status of consumers and regional variations are important which needs to be studied for addressing resource base safe food production help the strategic reduction of food insecurity in the country by 2030. Res. Agric., Livest. Fish.4(1): 29-36, April 2017